Rudimentary Horn Pregnancy with Intrauterine Fetal Death - RC, Laxmi; Nagar, Puspa; Sribastava, Madhiri (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v5i1.5063 NJOG 2010 Jul-Aug; 5(1): 53-54